Upgrading and fixing a PC : in easy steps - Yarnold, Stuart (In Easy Steps Limited, 2011)
Enables readers to keep their computers at the cutting-edge by explaining how to replace components and add new ones. Simple, illustrated instructions and sidebars teach users to identify, locate, and install the relevant parts to make their PCs faster, more versatile, and more powerful. Both a learning tool and an investment, this guide even provides a money-saving tutorial on various buying options and a separate chapter on troubleshooting nasty problems